2018
DOI: 10.1002/pat.4356
|View full text |Cite
|
Sign up to set email alerts
|

High‐flux PVDF membrane incorporated with β‐cyclodextrin modified halloysite nanotubes for dye rejection and Cu (II) removal from water

Abstract: The application of polyvinylidene fluoride (PVDF) membrane is impeded by its intrinsic hydrophobic property. In this work, a series of novel membranes were fabricated by blending different contents of β‐cyclodextrin modified halloysite nanotubes (β‐CD‐HNTs) into the casting solution. Elemental mapping images confirmed the good dispersion of β‐CD‐HNTs in the PVDF membrane matrix. The microstructure of membrane was improved as revealed by the morphological characterizations. Besides, the permeation and separatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 44 publications
(86 reference statements)
0
3
0
Order By: Relevance
“…For higher PVP loading (3wt%), the addition of GO-Ag composite (0.15wt%) results in polarity and flux enhancement [85]. With the incorporation of just 0.36 wt.% of β-CD-HNTs, the water flux experiences a slight yet remarkable boost [86]. These comparisons provide further insight for conducting deeper experiments.…”
Section: (A) (B)mentioning
confidence: 82%
“…For higher PVP loading (3wt%), the addition of GO-Ag composite (0.15wt%) results in polarity and flux enhancement [85]. With the incorporation of just 0.36 wt.% of β-CD-HNTs, the water flux experiences a slight yet remarkable boost [86]. These comparisons provide further insight for conducting deeper experiments.…”
Section: (A) (B)mentioning
confidence: 82%
“…Though membrane-based technology has been widely considered as clean and environmentally benign technology, 64–66 solvent extraction being conventional and easily adoptable at a large scale has been utilized throughout the present investigation. For the estimation of thorium, 283.231 nm, 283.730 nm and 401.913 nm analytical lines were chosen.…”
Section: Resultsmentioning
confidence: 99%
“…Even at very low filler content in PVDF polymer could improve the membrane properties and performance [55]. In the same filtration method, PMC0.3, PMCB0.3, and PMCC0.3 have a better rejection of dye than modified PVDF membrane with GO/ LiCl [4], Cu 2 S nanoparticles [52], and Fe 3 O 4 @XG [1], also comparable with PVDF/-CD-HNTs [56]. This research revealed that cellulose, cellulose benzoate, and cellulose citrate screw pine leaves can be used as fillers for PVDF membrane which gave a comparable membrane performance with inorganic filler.…”
Section: Pvdf/spcb and Pvdf/spccmentioning
confidence: 88%